Garlic-inspired trisulfide linkers for thiol-stimulated H2S release. Issue 57 (3rd July 2017) - Ercole, Francesca; Whittaker, Michael R.; Halls, Michelle L.; Boyd, Ben J.; Davis, Thomas P.; Quinn, John F.
Abstract : Garlic-inspired cholesterol-mPEG conjugates incorporating a trisulfide linkage have the ability to cleave upon exposure to thiols with a concomitant release of H2 S. Abstract : Garlic-derived polysulfides ( e.g., diallyl trisulfide, DATS) act as potent donors of the cell-signalling mediator H2 S when exposed to endogenous thiols. Inspired by this chemistry, we incorporated a trisulfide linkage into a conjugate comprising an mPEG tail and a cholesteryl head via thiol-mediated fragmentation chemistry. The synthesized conjugate releases H2 S upon exposure to thiol even at intracellular levels.